Risk factors of work-related musculoskeletal disorders among domestic waste collectors in Shah Alam / Nurkhalila Nuri - Nuri, Nurkhalila (Faculty of Health Sciences, 2015)
Introduction: Musculoskeletal disorder is one of the leading causes of occupational injury, illness and disability within many countries and different occupations. Work related musculoskeletal disorder among municipal waste collectors has been reported widely in several studies due to manual handling and also requires repeated heavy physical activities. Some recommendation may be derived from this study that may reduce or alleviate the problems of WMSDs among waste collectors. Methodology: A crosssectional study among 55 waste collectors of domestic contractor services under Shah Alam City Council was conducted to identify the Work Related Musculoskeletal Disorders (WMSDs) risk factors. The data were collected by using Modified Nordic Questionnaires and video recording in order to record the entire body movement and postures during working session. The questionnaires were used to identify Demographic data, occupational information and body part affected with WMSDs signs and symptoms. An Ovako Working Analysing System (OWAS) was used to identify the posture among waste collectors during their working task by reviewing the all the videos and focused mainly on back, arms, legs and loads of the waste collectors. Result: The results shows that high prevalence of musculoskeletal disorders symptoms among domestic waste collectors in Shah Alam were affected on lower back pain (n=40; 72.7%), shoulders pain (n=25; 45.4%) and knees pain (n=24; 43.6%). There was a significant association between age and period of working with neck pain, wrists or hands pain and ankles or feet pain. Neck pain and wrists or hands pain were significantly associated with age with (p=0.02) while ankles or feet pain was significantly associated with period of working with (p=0.05). Conclusion: The OWAS score showed the action required is under Category 2. This indicated that the corrective action is required in the near future. In addition, we can conclude that most of the workers are faced towards ergonomic hazards as they need to work in manual handling and repetitive task